2018
DOI: 10.1111/clr.13373
|View full text |Cite
|
Sign up to set email alerts
|

High risk of peri‐implant disease in periodontal Ehlers–Danlos Syndrome. A case series

Abstract: ObjectivesPeriodontal Ehlers–Danlos syndrome (pEDS) has recently been delineated as a molecularly defined cause of early severe periodontitis. Here we report that implant treatment failed in three affected individuals from one family.Materials and MethodsLongitudinal data before and after implant treatment were examined for three individuals with genetically confirmed pEDS in the course of a large‐scale pedigree analysis.ResultsMost detailed information was available for individual 1 in whom first periodontal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Kapferer-Seebacher et al 1 reported on 93 patients with pEDS; our family's clinical features were similar ( Table 1). Dental implants have been reported to be successful in patients with other forms of EDS, but pEDS has shown worse results, 2 as in the father of our family, whose implants lasted < 1 year.…”
mentioning
confidence: 73%
“…Kapferer-Seebacher et al 1 reported on 93 patients with pEDS; our family's clinical features were similar ( Table 1). Dental implants have been reported to be successful in patients with other forms of EDS, but pEDS has shown worse results, 2 as in the father of our family, whose implants lasted < 1 year.…”
mentioning
confidence: 73%
“…Rinner et al (2018) reported a series of three familial cases of periodontal-type EDS with implant failures secondary to severe peri-implantitis despite appropriate periodontal management. The bone loss was amplified by the procedure, leading to the conclusion that there is a strong mechanical influence on the implant prognosis in these three patients [22]. Therefore, the biological mechanisms of osseointegration seem to be preserved without major and specific complications in the context of the EDS; however, clinical studies involving larger cohorts of patients are needed.…”
Section: Surgical Managementmentioning
confidence: 99%
“…The main challenge in oral cares of patients with EDS is the preservation of a functional dentition as long as possible and prevention of any infectious pathology, which can be addressed by regular specialized follow-ups and implementation of adapted. Early preventive and conservative care and motivation for oral hygiene to prevent complex or potentially iatrogenic fixed or adjunctive prosthetic rehabilitation are also essential and integrated in the treatment plan [13,16,22].…”
Section: Oral Management Of Patients With Eds General Principlesmentioning
confidence: 99%
“…38 Recently, leukencephalopathy and peri-implant disease were described as additional features of pEDS. 39,40 In 2016, bi-allelic AEBP1 mutations were described in an autosomal recessive EDS variant, featuring joint hypermobility with joint dislocations, hyperextensible, translucent and redundant skin, poor wound healing with abnormal scarring, easy bruising and gastrointestinal, urogenital, cardiovascular and skeletal abnormalities. Its features overlap with several EDS types, particularly cEDS, mcEDS and spEDS.…”
Section: Classification and Nosologymentioning
confidence: 99%
“…Often this is not possible and therefore there is still room for new types. This is, among other things, due to: -the clinical overlap between many of these EDS types Journal of Biomedicine and Translational Research, 5 (2) 2019, [34][35][36][37][38][39][40][41][42][43][44][45][46] -absence of a pathogenic variant in any of the known EDS associated genes in an important proportion of EDS patients. -the presence of associated features which do not fit into one of the existing types.…”
Section: Introductionmentioning
confidence: 99%